Optimization of heat transfer at the surface of parabolic fins by genetic Algorithm (Bangladesh Journal of Scientific and Industrial Research, 2017)
Thermal fins are extended surfaces like longitudinal, radial, and cylindrical fins. They are used for the improvement of heat transfer between an object and fluid. Fins can be applied in many processes of objects cooling such as electrical appliances, many types of engines, transformers, chemical industry, air conditioning, heat exchangers and the industries of energy exchanges. This matter is one of the main results of paying attention to this issue. Therefore, this study examined the optimization of fin heat transfer by using a genetic algorithm and consideration of Nusselt number and hydraulic resistance as the objective function. In this paper, we investigated the optimization of the fin to maximize the heat transfer and also to minimize the hydraulic resistance. The results of this study can be effective in term of technical and economic efficiency in the industry of fin transformer. The stimulation and library method has been used to collect data. The results indicated that if the hydraulic resistance was limited to a specific value, using wavy fins will not improve the device heat.Bangladesh J. Sci. Ind. Res. 52(4), 325-330, 2017